Competition in the tridimensional urban fresh produce retail market : the case of the Tshwane metropolitan area, South Africa - Louw, Andre (University of Pretoria, 2013)
Dissertation (MSc(Agric) (Agricultural Economics))--University of Pretoria, 2007.